Persepsi Peserta Didik Tentang Penerapan Model Pembelajaran Berbasis Projek Pemanfaatan Teknologi Informasi Dan Komunikasi - Syahid Faturrojak; Dewi Septiani Kurniasih (Lembaga Pengembangan Kinerja Dosen, 2021)
Information and Communication Technology is one of the new developments in the world of education which is currently being felt in every line of life. The purpose of this study is to describe the use of information and communication technology or ICT on students' perceptions of the application of Project Based Learning in the concept of acid and base indicators. The type of research used in this study is a quantitative research with a descriptive survey method. Based on the results of data processing and discussion, it is known that the use of information and communication technology affects students' perceptions of the application of project-based learning models.